New and Future Developments in Catalysis : Catalysis by Nanoparticles. - Suib, Steven L. (Elsevier Science, 2013)
New and Future Developments in Catalysis is a package of seven books that compile the latest ideas concerning alternate and renewable energy sources and the role that catalysis plays in converting new renewable feedstock into biofuels and biochemicals. Both homogeneous and heterogeneous catalysts and catalytic processes will be discussed in a unified and comprehensive approach. There will be extensive cross-referencing within all volumes. The use of catalysts in the nanoscale offers various advantages (increased efficiency and less byproducts), and these are discussed in this volume along.